(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals the concept of pedagogical technique, describes information about the methods of influence of a teacher on a person and a team, ways of forming pedagogical techniques. Pedagogical mastery is a multifaceted and broad-minded concept, the formation and development of which will take a long time. The formation and development of pedagogical qualities and professional pedagogical skills of a teacher is a process that has internal contradictions and is influenced by many factors